Comprehensive Care and Challenges of Alzheimer’s Disease - Guerrero , Marcela; Ponti , Liliana; Sebastián , Gabini; Lorincz , Andrea (SCT Proceedings in Interdisciplinary Insights and Innovations, 2025)
Introduction: Alzheimer’s disease (AD), described by Alois Alzheimer, constituted the most prevalent type of dementia, accounting for 60% to 70% of global cases. This progressive neurodegenerative disorder affected higher cognitive functions such as memory, language and reasoning, causing a gradual loss of autonomy. Its prevalence doubled with age, especially in those over 65 years of age. AD had a significant impact on the quality of life of patients and their caregivers, posing increasing challenges for healthcare systems. Development: AD was characterized by progressive cognitive, physical and social deterioration, with stages ranging from pre-dementia to severe dementia. In its advanced stages, patients became completely dependent and vulnerable to complications such as pressure ulcers and infections. Comprehensive care strategies highlighted the need for multidimensional approaches, encompassing physical, psychological and social interventions. Caregivers, mostly family members, faced a significant emotional burden, which highlighted the importance of providing them with support. For their part, multidisciplinary health teams, led by trained nursing professionals, played a crucial role in disease management. Conclusions: AD demanded a comprehensive approach focused on improving the quality of life of the patient and their caregivers. Although there was no cure, interventions focused on quality of life and humanized care were essential. Research and public policies continued to be fundamental to address the growing impact of this disease on society